2021
DOI: 10.1002/slct.202101086
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, DFT Study, Molecular Docking and Drug‐Likeness Analysis of the New Hydrazine‐1‐Carbothioamide, Triazole and Thiadiazole Derivatives: Potential Inhibitors of HSP90

Abstract: In this research, the new hydrazine-1-carbothioamides (IC32 and IC34) having unsubstituted benzimidazole skeleton were converted to 1, 2, 4-triazole derivatives (IC42 and IC44) by Ncyclization reaction using the microwave-assisted synthesis method in the basic medium with high efficiency in a short time. 2-Amino-1,3,4-thiadiazole derivatives (IC52 and IC54) were obtained from the carbothioamides in the acidic medium by S-cyclization using the conventional method. The structure of all compounds was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…From Figure 13, it is observed that BBT is working in the bioavailability radar. The Brain or Intestinal Estimated permeation method (BOILED‐EGG) is a precise and notable method for drug discovery and growth in literature [65] . As seen from Figure 14, BBT molecule is originated to be nearer to the BBB.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 13, it is observed that BBT is working in the bioavailability radar. The Brain or Intestinal Estimated permeation method (BOILED‐EGG) is a precise and notable method for drug discovery and growth in literature [65] . As seen from Figure 14, BBT molecule is originated to be nearer to the BBB.…”
Section: Resultsmentioning
confidence: 99%
“…In silico techniques have been widely applied to drug screening. [16][17][18][19] Various computational tools and methods may be used to identify the candidate drug from other compounds depending on multiple features such as physicochemical/pharmacokinetic parameters and drug-likeness. Herein, QM calculations were carried out for the synthesized compounds to correlate their structures with biological activities via analysis of the FMOs and quantum chemical descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…The DFT is very useful since it provides opportunity to make calculations in a very large scale, in a shorter time with high accuracy. There are many studies performed with DFT [15,16]. By using the ABINIT programme, which depends on the DFT, we saw that, RhBiSe exhibits all features of pyrite-marcasite family which belongs to TMDCs, such as good electronic properties with a narrow band gap, convenient optic properties, and elastic properties.…”
Section: Introductionmentioning
confidence: 99%